Good Governance: Exploring the Fragility and Components of Good Governance (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Nearly every major development agency now says that the promotion of good governance is an important aspect of its objective. Despite this accord, good governance is an extraordinarily elusive goal it signifies different things to various organisations and to various players within them. This paper reviews the approach of donors and explores the concept of good governance. The study argues that, though often esoteric, methodological discussions have a real relevance to development policies because donor agencies regularly measure and evaluate the quality of governance, make sure that assistance is provided, try to design evidence-based policies and justify their focus on governance on the grounds, among other things, that better governance promotes e-government Each of these undertakings is questioned by the fragility of the concept of good governance. Future study would do well to break up the concept of good governance and to focus on its many components as defined above (e.g., democracy, the rule of law, efficient public management).